10. The Use of Lower Organisms. Issue 2 (May 2014) - Balls, Michael
Lower organisms can be particularly useful as high discrimination models in fundamental research, but cannot offer the high fidelity required when specific questions are asked about humans in health and disease, and about their responses to drugs and other chemicals